Reconstruction of Tragus and External Auditory Meatus using Remnant Auricle during Microtia Reconstruction - Li, Gao-feng; Hu, Yi-gao; Ding, Wei; Tan, Jun; Chen, Xin; Luo, Tao; Zhang, Bo; Liu, Xiao-jia (Facial Plastic Surgery, 2018)
This article investigates an effective method with which to reconstruct the tragus and external auditory meatus for microtia reconstruction. The external ear was reconstructed using a delayed postauricular skin flap in patients with congenital microtia. After the first stage of delaying the postauricular skin flap and the second stage of otoplasty with ear framework fabricated from autogenous rib cartilage draping with the delayed skin flap, the third stage involved tragus and external auditory meatus canaloplasty. After designing the remnant auricle flap, the lower part was trimmed and the tragus was reconstructed. The upper part was trimmed into a thin skin flap, which was rotated and used to cover the hollowed wound posterosuperior to the tragus so as to mimic the external auditory meatus. If remnant wounds were present, skin grafting was conducted. In total, 121 patients with congenital microtia were treated from March 2010 to March 2016. The reconstructed tragus and external auditory meatus were well formed, and all wounds healed well. No severe complications such as flap necrosis occurred. Six months postoperatively, the morphology of the reconstructed tragus and external auditory meatus was good. Overall, the patients and their families were satisfied. The use of remnant auricle to reconstruct the tragus and external auditory meatus is an effective auricular reconstruction technique.
Keywords: microtia; auricular reconstruction; tragus; external auditory meatus; remnant auricle